1980
DOI: 10.1002/jsfa.2740310906
|View full text |Cite
|
Sign up to set email alerts
|

Rapeseed meal and egg taint: The role of sinapine

Abstract: Agricultural Research Council Food Research Institute, Colney Lane, Norwich, Norfolk NR4 7UANeither the administration of sinapine bisulphate in the diet, nor the repeated intramuscular or intravenous injection of large doses of this substance, reduced the ability ofchicks or laying hens to oxidise trimethylamine (TMA), as measured by the activity of TMA oxidase in hepatic microsomes or the amounts of 14C-TMA oxide that appeared in the plasma after the infusion of a standard dose of 14C-TMA. Thus, in contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Sinapine causes an unpleasant flavor in the meat and milk of animals fed on canola/B. napus (Pearson et al 1980) and the bitter flavor of sinapine results in poor palatability for livestock (Ismail et al 1981). Moreover, consumption of sinapine in canola meal by brown-shelled egg layers that are deficient in trimethylamine oxidase imparts a fishy odour to the eggs.…”
Section: Introductionmentioning
confidence: 98%
“…Sinapine causes an unpleasant flavor in the meat and milk of animals fed on canola/B. napus (Pearson et al 1980) and the bitter flavor of sinapine results in poor palatability for livestock (Ismail et al 1981). Moreover, consumption of sinapine in canola meal by brown-shelled egg layers that are deficient in trimethylamine oxidase imparts a fishy odour to the eggs.…”
Section: Introductionmentioning
confidence: 98%
“…Sinapine, for instance, has a bitter taste and causes an unpleasant flavor in meat and milk of animals. [8] Hence, there are efforts to reduce the amount of phenolic compounds, in particular sinapate esters, by conventional and molecular breeding approaches to establish rape seed as a source of food-grade protein. [9] Motivated by the pronounced interest in this class of compound, several methods for the analysis of phenolic choline esters from seeds have been proposed in the past.…”
Section: Introductionmentioning
confidence: 99%
“…This may be caused by the occurrence of the unpleasant "fishy" odour of eggs from some hens fed rapeseed meal. In reviews on the occurrence of egg taint, Pearson et al (1980) and Butler et al (1982) found that it is related to the presence of sinapine in rape seed and reduced trimethylamine oxidaze activity in the liver of those hens that lay brown-shelled eggs. These layers lack the gene that is responsible for the degradation of trimethylamine, a compound with a fishy odour, that is formed in the bacterial hydrolysis of synapine.…”
Section: Introductionmentioning
confidence: 99%